THE EFFECTIVENESS OF THE DRILL AND PRACTICE METHOD ON MENSTRUAL PERSONAL HYGIENE BEHAVIOR IN TEENAGERS WITH INTELLECTUAL DISABILITIES AT EXTRAORDINARY SCHOOL (SLB) SHANTI KOSALA MASTRIP NGANJUK - Binti Asrofin; Efi Kristiana (Journal for Quality in Women's Health, 2023)
The cognitive limitations of adolescents with intellectual disabilities make them more at risk of experiencing reproductive health problems, one of which is menstruation which requires specific personal hygiene behaviors.  The purpose of this study was to measure the effectiveness of the drill and practice method on menstrual personal hygiene behavior in adolescents with intellectual disabilities at Extraordinary school (SLB) Shanti Kosala Mastrip Nganjuk. The model used in this study was a quasi-experimental by twice measurements. Before and after being given menstrual personal hygiene material, the lowest behavior score was 37.5 to 55 and the highest score was 77.5 to 77.5 with an average score of 57.90 to 74.90. Analysis result is known that the Sig.(2-tailed) value is 0.000 with α(0.05)  The provision of menstrual personal hygiene material using the drill and practice method can improve menstrual personal hygiene behavior in teenage women at SLB Shanti Kosala Mastrip Nganjuk.